Penerapan Head Up 30̊ terhadap Penurunan Kapasitas Adaptif Intrakranial pada Pasien dengan Hidrosefalus Post VP Shunting di RSUD Dr. Moewardi Surakarta - Erlena Nur Intan; Sri Puguh Kristiyawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Hydrocephalus increases cerebrospinal fluid due to either excessive production or impaired absorption, often accompanied by increased intracranial pressure. In Indonesia, hydrocephalus affects 10 out of every 1,000 newborns annually. In adolescents and adults, toxoplasmosis is the most common cause. Among infant cases, 46% result from brain development abnormalities, 50% from subarachnoid hemorrhage and meningitis, and less than 4% from posterior fossa tumors. Central Java reports the highest rate of toxoplasmosis at 10%. Common signs and symptoms of hydrocephalus include increased cerebrospinal fluid, seizures, irritability, headaches, vision problems, and head enlargement. To improve reduced intracranial adaptive capacity caused by cerebrospinal fluid obstruction, nurses can apply a 30° head-up therapy. This intervention helps lower intracranial pressure and improve brain oxygenation. the effectiveness of 30° head-up positioning in addressing decreased intracranial adaptive capacity in post-VP shunting hydrocephalus patients. The nursing intervention was implemented on Mrs. S using the 30° head-up position. As a result, the patient reported reduced headache, and her blood pressure decreased to 135/90 mmHg.